2018
DOI: 10.1159/000486756
|View full text |Cite
|
Sign up to set email alerts
|

Negative Aging Stereotypes Disrupt both the Selection and Execution of Strategies in Older Adults

Abstract: Background: Age-based cognitive deficits are exacerbated by stereotype threat effects (i.e., the threat of being judged as cognitively incapable due to aging). We tested whether age-based stereotype threat effects can occur via impair- ing older adults’ ability to select the best strategy and/or to execute strategies efficiently. Methods: Older adults (age range: 64.3–89.5 years) were randomly assigned to a stereotype threat or control condition before taking an episodic memory task. They encoded pairs of conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
(84 reference statements)
2
10
0
1
Order By: Relevance
“…That older adults used the better strategy less often and executed available strategies less efficiently under threat here are consistent with previous proposals or empirical findings (e.g., Hess et al, 2003;Lemaire et al, 2018). Indeed, like Hess et al who found some indirect evidence that threat reduced the use of more efficient memory strategies, we also inferred from our data (Experiment 1) that threat disrupted the use of more efficient arithmetic strategies.…”
Section: How Does Stereotype Threat Impairs Older Adults' Performance?supporting
confidence: 93%
“…That older adults used the better strategy less often and executed available strategies less efficiently under threat here are consistent with previous proposals or empirical findings (e.g., Hess et al, 2003;Lemaire et al, 2018). Indeed, like Hess et al who found some indirect evidence that threat reduced the use of more efficient memory strategies, we also inferred from our data (Experiment 1) that threat disrupted the use of more efficient arithmetic strategies.…”
Section: How Does Stereotype Threat Impairs Older Adults' Performance?supporting
confidence: 93%
“…The main predictions of this hypothesis are interactions between culture and effects of stereotype threat on participants' performance and strategy choices. Effects of stereotype threat on participants' performance (i.e., more accurate estimates and faster speed in control than in stereotype threat condition) should be found in French participants, replicating previous findings (e.g., Nicolas et al, 2020;Lemaire et al, 2018). Moreover, these effects should be smaller, or even non-existent, in Indian participants who, relative to French participants, would obtain smaller performance differences, or even no differences, between stereotype threat and control conditions.…”
Section: Hypotheses and Predictionssupporting
confidence: 81%
“…Participants under stereotype threat and control conditions received different instructions (see Supplementary Material). These instructions were adopted from previous studies ( Lemaire et al, 2018;Mazerolle et al, 2012;Nicolas et al, 2020), and were used here as they proved effective in manipulating stereotype threat in these past studies.…”
Section: Methodsmentioning
confidence: 99%
“…La literatura internacional documenta que la vejez se relaciona con estereotipos negativos (Bustillos-López & Fernández-Ballesteros, 2012;de Oliveira Moreira, 2011;Lasagni et al, 2013;Lemaire, Brun, Régner, & Régner, 2018;Mariluz, 2011;Melero, 2007;Menéndez, Cuevas, Pérez, & Lorence, 2016;Monchietti & Sánchez, 2008;Rello, López, & Muñoz, 2018). Butler acuñó el término ageism o edadismo para referirse al conjunto de estereotipos, discriminaciones y segregaciones que se aplican a los viejos, en función de su edad (Butler, 2008;Rice, 1997;Salvarezza, 2002).…”
Section: ____________________________________________________________unclassified